2018
DOI: 10.11646/phytotaxa.350.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Land Plants Today: Index of Liverworts & Hornworts 2015–2016

Abstract: A widely accessible list of known plant species is a fundamental requirement for plant conservation and has vast uses. An index of published names of liverworts and hornworts between 2015 and 2016 is provided as part of a continued effort in working toward maintaining an updated world checklist of these groups. The list herein includes 64 higher taxon names, 225 specific names, 35 infraspecific names, two infrageneric autonyms and 21 infraspecific autonyms for 2015 and 2016, including also names of fossils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This index follows on from decades of previous bryophyte (mosses, liverworts, hornworts) specific indices. Söderström et al (2018) summarized the many ongoing nomenclatural indexing efforts as well as the many valuable historical contributions.…”
Section: Introductionmentioning
confidence: 99%
“…This index follows on from decades of previous bryophyte (mosses, liverworts, hornworts) specific indices. Söderström et al (2018) summarized the many ongoing nomenclatural indexing efforts as well as the many valuable historical contributions.…”
Section: Introductionmentioning
confidence: 99%
“…This index follows on from decades of previous bryophyte (mosses, liverworts, hornworts) specific indices. Söderström et al (2018) summarized the many nomenclatural indexing and similar projects, including: TROPICOS (https://www.tropicos.org/home); Index Hepaticarum, which includes all effectively published liverwort epithets spanning 12 volumes with the closing date of 1973 (http://www.ville-ge.ch/musinfo/bd/cjb/hepatic/index.php); Index of Hepatics by Crosby & Engel (2006) providing an equally valuable nomenclatural resource and catalogue of names at all ranks for liverworts and hornworts published during 1974 to 2000; and the recent indices of the citations for names published for bryophytes for the years [2001][2002][2003][2004] (Crosby & Magill 2005) and 2005 (Crosby & Magill 2006). The current index continues the series in the form of an Index for Liverworts and Hornworts now spanning over a decade (von Konrat et al 2010, Söderström et al 2012, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…TYPE: "India, Eastern Himalaya, Arunachal Pradesh, West Siang District, Liromoba, 28°04' N 94°29' E, ca 550m, 14.09.2011, S. Singh Deo 51281A (Holotype & Isotype: CAL)". NOTE: The index for 2015-2016 (Söderström et al (2018) reported the description published in Singh Deo & Singh (2016) but this publication was probably issued at the end of the year (it was issue 4 of 4 issues annually) while the publication cited for the name here was published in June 2016 fide title page.…”
Section: Introductionmentioning
confidence: 99%
“…This index follows on from decades of previous bryophyte (mosses, liverworts, hornworts) specific indices. Söderström et al (2018) summarized the many nomenclatural indexing and similar projects, including: TROPICOS (https://www.tropicos.org/home); Index Hepaticarum, which includes all effectively published liverwort epithets spanning 12 volumes with the closing date of 1973 (http://www.ville-ge.ch/musinfo/bd/cjb/hepatic/index.php); Index of Hepatics by Crosby & Engel (2006) providing an equally valuable nomenclatural resource and catalogue of names at all ranks for liverworts and hornworts published during 1974 to 2000; and the recent indices of the citations for names published for bryophytes for the years 2001-2004(Crosby & Magill 2005 and 2005 (Crosby & Magill 2006). The current index continues the series in the form of an Index for Liverworts and Hornworts now spanning over a decade (von Konrat et al 2010, Söderström et al 2012, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Frullania heinrichsii Gradst., Espinoza-Prieto et J. (Söderström et al (2018) reported the description published in Singh Deo & Singh (2016) but this publication was probably issued at the end of the year (it was issue 4 of 4 issues annually) while the publication cited for the name here was published in June 2016 fide title page.…”
Section: Introductionmentioning
confidence: 99%